Herding and contrarian behavior in financial markets: an Internet experiment - Drehmann, Mathias; Oechssler, Joerg; Roider, Andreas (American economic review, 2005)
We report results of an Internet experiment designed to test the theory of informational cascades in financial markets (Christopher Avery and Peter Zemsky, 1998). More than 6,400 subjects, including a subsample of 267 consultants from an international consulting firm, participated in the experiment. We find that the presence of a flexible market price prevents herding. The presence of contrarian behavior distorts prices, however, and even after 20 decisions, convergence to the fundamental value is rare. We also report some interesting differences with respect to subjects' fields of study. Reassuringly, the behavior of the consultants turns out to be not significantly different from that of the remaining subjects.